Te Whakapakari te Mana Tangata: The Politics and Process of Research for Maori - Teariki, Christine; Spoonley, Paul; Tomoana, Ngahiwi (The Dept., 1992)
Keywords: research; research policy

Hā Ora: Reflecting on a Kaupapa Māori community engaged co-design approach to lung cancer research - Kidd, Jacquie; Cassim, Shemana; Rolleston, Anna; Keenan, Rawiri; Lawrenson, Ross; Sheridan, Nicolette; Warbrick, Isaac; Ngaheu, Janette; Hokowhitu, Brendan (2021)
Co-designed research is gaining prominence within the health care space. Community engagement is a key premise of co-design and is also particularly vital when carrying out kaupapa Māori research. Kaupapa Māori describes a “by Māori, for Māori” approach to research in Aotearoa/New Zealand. This article discusses the research process of Hā Ora: a co-design project underpinned by a kaupapa Māori approach. The objective was to explore the barriers to early presentation and diagnosis of lung cancer, barriers identified by Māori. The team worked with four rural Māori communities, with whom we aimed to co-design local interventions that would promote earlier diagnosis of lung cancer. This article highlights and unpacks the complexities of carrying out community- engaged co-design with Māori who live in rural communities. In particular, we draw attention to the importance of flexibility and adaptability in the research process. We highlight issues pertaining to timelines and budgets, and also the intricacies of involving co-governance and advisory groups. Overall, through this article, we argue that health researchers need to prioritise working with and for participants, rather than on them, especially when working with Māori communities.
Keywords: co-governance; health inequity; kaupapa māori; research

Adaptation and implementation processes of a culture-centred community-based peer-education programme for older Māori - Simpson, Mary Louisa; Ruru, Stacey; Oetzel, John; Meha, Pare; Nock, Sophie; Holmes, Kathrine; Adams, Hariata; Akapita, Ngapera; Clark, Marama; Ngaia, Kawarau; Moses, Reuben; Reddy, Rangimahora; et al. (Implementation Science Communications, 2022)
Health inequities experienced by kaumātua (older Māori) in Aotearoa, New Zealand, are well documented. Examples of translating and adapting research into practice that identifies ways to help address such inequities are less evident. The study used the He Pikinga Waiora (HPW) implementation framework and the Consolidated Framework for Implementation Research (CFIR) to explore promising co-design and implementation practices in translating an evidence-based peer-education programme for older Māori to new communities.
Keywords: health inequity; research